How to Resolve the Overlapping Maritime Claims in International Law? Comparing Barbados Trinidad vs Tobago case and Indonesia-Malaysia Cases - Ramadhan, Arif; Kareem, Mohammad Abdul Latief (Universitas Negeri Semarang, 2022)
Barbados and Republic of Trinidad and and Tobago are two statesthay facing each other andlocated in Carribian sea. Since along long time ago, these twostates often mixed up withdispute about maritimes boundaries or about the shing of each states, such as when the shing fron Barbados reputedinfringe the boundaries of Republic Trinidad and Tobago. Like this case above was often happened thay nally must be nished with helped by international law. Aswe know that in that Continental shelf with drawnmust 200 nm from the outer states boundaries, and both of them has claimed that they had been fallowed the rules, but thereare still happen an argue between them. How this dispute happened until reached the agreement, how the steps andhow the result of the agreement will be explained in this paper.